Upaya Pencegahan Tawuran Yang Terus Menerus Terjadi Di SMA Swasta Eria Medan - Tasya Ananda Putri Harahap; Ananda Viranda; Auliya Putri Riski; Annisa Ayu Safitri; Nur Fadilla; Anggelina Labora Dorasi Lumban Gaol (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
The rise of brawls between students in various cities in Indonesia, especially those carried out by students at the high school level, has become a phenomenon that frequently appears and makes headline news in various mass media. In this research, the author examines efforts to prevent brawls that continuously occur at Eria Private High School, Medan. The aim of this research is to provide a solution so that brawls cannot recur as before. In this research we used qualitative research methods, using a descriptive approach. Where data collection techniques in this research were carried out using observation, interviews, documentation, as well as from various other articles. The results of this research reveal what preventive measures have been taken to deal with brawls that often occur at Eria Private High School, Medan.